2021
DOI: 10.3389/fphar.2021.675907
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fibrotic Effects of Low Toxic Microcystin-RR on Bleomycin-Induced Pulmonary Fibrosis: A Comparison with Microcystin-LR

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial pulmonary disease characterized with radiographically evident pulmonary infiltrates and extracellular matrix deposition with limited treatment options. We previously described that microcystin-LR (MC-LR) reduces transforming growth factor (TGF)-β1/Smad signaling and ameliorates pulmonary fibrosis in bleomycin (BLM)-induced rat models. In the present study, we further demonstrate that microcystin-RR (MC-RR), an MC congener with lower toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the subacute stage, the proliferation and differentiation of fibroblasts and the expression of pro-fibrotic cytokines will appear in the lesion area; there will be a large amount of extracellular matrix deposition and fibrotic lesions [ 35 ]. The BPF mouse model and found that the lungs of the model group showed varying degrees of alveolar structural damage, inflammatory cell infiltration, and a large amount of collagen-based extracellular matrix deposition [ 36 ]. The gene expression test results showed that mouse lung tissue interleukin, collagen gene connective tissue growth factor, and transforming growth factor were all increased to varying degrees compared with those in the normal control group, which was consistent with the histopathological changes of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…In the subacute stage, the proliferation and differentiation of fibroblasts and the expression of pro-fibrotic cytokines will appear in the lesion area; there will be a large amount of extracellular matrix deposition and fibrotic lesions [ 35 ]. The BPF mouse model and found that the lungs of the model group showed varying degrees of alveolar structural damage, inflammatory cell infiltration, and a large amount of collagen-based extracellular matrix deposition [ 36 ]. The gene expression test results showed that mouse lung tissue interleukin, collagen gene connective tissue growth factor, and transforming growth factor were all increased to varying degrees compared with those in the normal control group, which was consistent with the histopathological changes of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Histological characteristics documentation and the prevalence of lung parenchymal lesions associated with original tissue loss and collagen fiber accumulation was studied by the Sirius Red, or Elastica-Van Gieson method [47].…”
Section: Histochemical Methods For Detection Of Elastic and Collagen ...mentioning
confidence: 99%
“…Bleomycin (BLM) has a significant effect on proliferation of collagen fibers (Maeda et al, 2016 ; Wang et al, 2021 ). It can induce the proliferation of fibroblasts and the numerous accumulation of collagen fibers (Willenborg et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%